2017
DOI: 10.1063/1.5013235
|View full text |Cite
|
Sign up to set email alerts
|

Flexible magnetoelectric transducer with high magnetic field sensitivity based on Metglas/poly(vinylidene fluoride) heterostructures

Abstract: In this paper, the flexible magnetoelectric (ME) transducer consisting of FeSiB (Metglas)/poly(vinylidene fluoride) (PVDF) is presented, whose ME coupling characteristics and ME sensing performance under different bend status have been investigated. It is found that an appropriate size of transducers is propitious to the ME coupling characteristics due to the demagnetization effect. In addition, with increase the bending angle (θ) of transducers from 0° to 50°, the magnetoelectric voltage coefficient (MEVC) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In this sense, a wide range of composites based on polymer matrices ensure flexibility, high insulation (large band gap), and high breakdown fields, filled with high permittivity complex oxide inclusions; for example, ferroelectrics as BaTiO 3 (BT) and its solid solutions, Pb­(Zr, Ti)­O 3 , and so forth have been proposed in the past years. , Polymer–inorganic hybrids produced from solution-based technologies have the advantage of using a low thermal budget and easy processing steps as well as the possibility to be implemented in printing technologies, providing flexible components and circuits compliant with non-planar surfaces, easy integration, and low weight. Among the proposed polymer matrices, ferroelectric PVDF or its copolymers such as P­(VDF-TrFE) compounds are the most studied, due to their ferro-, piezo-, and pyroelectric character found in specific molecular arrangements, thus being interesting for flexible pressure and temperature sensors and for their hysteretic polarization switching properties (memory effect), magnetoelectric properties when filled with magnetic particles, and so forth. , Higher permittivity with respect to those of the pure polymers (ε r of a few units) is also required in flexible mechanical or thermal energy-harvesting applications developed in capacitive configurations, in which the device should first store the collected piezo-, pyro-, or triboelectric generated charges, which is further used by an external circuit. For both types of applications, in energy storage and energy conversion/harvesting, BaTiO 3 –PVDF flexible composites are the most frequently proposed materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a wide range of composites based on polymer matrices ensure flexibility, high insulation (large band gap), and high breakdown fields, filled with high permittivity complex oxide inclusions; for example, ferroelectrics as BaTiO 3 (BT) and its solid solutions, Pb­(Zr, Ti)­O 3 , and so forth have been proposed in the past years. , Polymer–inorganic hybrids produced from solution-based technologies have the advantage of using a low thermal budget and easy processing steps as well as the possibility to be implemented in printing technologies, providing flexible components and circuits compliant with non-planar surfaces, easy integration, and low weight. Among the proposed polymer matrices, ferroelectric PVDF or its copolymers such as P­(VDF-TrFE) compounds are the most studied, due to their ferro-, piezo-, and pyroelectric character found in specific molecular arrangements, thus being interesting for flexible pressure and temperature sensors and for their hysteretic polarization switching properties (memory effect), magnetoelectric properties when filled with magnetic particles, and so forth. , Higher permittivity with respect to those of the pure polymers (ε r of a few units) is also required in flexible mechanical or thermal energy-harvesting applications developed in capacitive configurations, in which the device should first store the collected piezo-, pyro-, or triboelectric generated charges, which is further used by an external circuit. For both types of applications, in energy storage and energy conversion/harvesting, BaTiO 3 –PVDF flexible composites are the most frequently proposed materials .…”
Section: Introductionmentioning
confidence: 99%
“…Among the proposed polymer matrices, ferroelectric PVDF or its copolymers such as P(VDF-TrFE) compounds are the most studied, due to their ferro-, piezo-, and pyroelectric character found in specific molecular arrangements, thus being interesting for flexible pressure and temperature sensors and for their hysteretic polarization switching properties (memory effect), magnetoelectric properties when filled with magnetic particles, and so forth. 7,8 Higher permittivity with respect to those of the pure polymers (ε r of a few units) is also required in flexible mechanical or thermal energy-harvesting applications developed in capacitive configurations, in which the device should first store the collected piezo-, pyro-, or triboelectric generated charges, which is further used by an external circuit. For both types of applications, in energy storage and energy conversion/ harvesting, BaTiO 3 −PVDF flexible composites are the most frequently proposed materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the study of ME effects in structures with layers of amorphous ferromagnetic alloys FeBSiC and piezo-polymers (vinilidene fluoridetrifluoroethylene) (PVDF) [6][7][8][9][10][11][12][13][14]. The ferromagnetic alloys FeBSiC in the form of ribbons with a thickness of 20-30 μm are made by ultrafast cooling, they possess magnetostriction λS ~ (20-30)•10 −6 , are saturated in weak magnetic fields HS ~50 Oe, and are characterized by small magnetic and electrical losses [15].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, researchers are particularly interested in achieving high α ME values at low frequencies to meet the requirements of detecting low-frequency weak magnetic fields. In this study, the results are compared with other reported low-frequency ME laminated composites prepared by partial bonding method, as illustrated in Figure . Through the implementation of vacuum packaging during the curing process, we successfully increased the value of α ME while simultaneously reducing the resonance frequency. This dual achievement holds significant benefits for the practical application of ME composite films, which have great advantages in low-frequency flexible devices.…”
Section: Resultsmentioning
confidence: 97%